Recombination-dependent replication: new perspectives from site-specific fork barriers. (December 2021) - Carr, Antony; Lambert, Sarah
Abstract : Replication stress (RS) is intrinsic to normal cell growth, is enhanced by exogenous factors and elevated in many cancer cells due to oncogene expression. Most genetic changes are a result of RS and the mechanisms by which cells tolerate RS has received considerable attention because of the link to cancer evolution and opportunities for cancer cell-specific therapeutic intervention. Site-specific replication fork barriers have provided unique insights into how cells respond to RS and their recent use has allowed a deeper understanding of the mechanistic and spatial mechanism that restart arrested forks and how these correlate with RS-dependent mutagenesis. Here we review recent data from site-specific fork arrest systems used in yeast and highlight their strengths and limitations.